Between Interest and Compliance: An Analysis of Factors Driving Tax Avoidance - Toni Yoyo; Vivin Hanitha (LPPM Universitas Buddhi Dharma, 2026)
The purpose of this study is to examine how tax avoidance is impacted by managerial ownership, independent commissioners, audit committees, CEO Compesation, and foreign ownership. This study employed a quantitative methodology using secondary data from corporate financial statements and annual reports. Purposive sampling was used to choose 180 firms that were listed on the Indonesia Stock Exchange between 2020-2025. Panel data regression was the method utilized for data analysis. The study's partial findings show that independent commissioners have a considerable negative impact on tax avoidance, whereas management ownership and foreign ownership have a significant beneficial impact. In the meanwhile, tax evasion is not much impacted by audit committees or CEO compensation. Concurrently, tax evasion is not significantly impacted by any of the independent variables. According to the coefficient of determination, 32.49% of the dependent variable may be explained by the research model, with other factors influencing the remaining portion. When making judgments about corporate tax policy, investors, management, and regulators may take ownership structure and corporate governance systems into account. This study suggests that these factors have an impact on tax avoidance techniques.